2019
DOI: 10.1111/lam.13156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Escherichia coli O157 and Salmonella spp. in solid bovine manure in California using real‐time quantitative PCR

Abstract: The occurrence of Escherichia coli O157 and Salmonella spp. in solid bovine manure was investigated through a multi‐county survey in California. Solid bovine manure samples (n = 91) were collected from 13 dairy farms located in multiple counties in California between June 2016 and August 2017. To quantify pathogens, DNA was extracted from bacteria in manure samples. Afterwards, the prevalence and levels of E. coli O157 and Salmonella spp. in solid bovine manure were determined by real‐time quantitative PCR (qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
6
3
Order By: Relevance
“…Salmonella were detected in PS (2017), DLE (2018), and SL (2018) treatments and further transferred to the amended soil samples. In support of our finding, 6.6% of solid bovine manure collected from dairy farms in California was positive of Salmonella (Chen et al, 2019). Salmonella has been detected in more than 80% of effluent bovine manure immediately post-commercial anaerobic digestion (Chiapetta et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Salmonella were detected in PS (2017), DLE (2018), and SL (2018) treatments and further transferred to the amended soil samples. In support of our finding, 6.6% of solid bovine manure collected from dairy farms in California was positive of Salmonella (Chen et al, 2019). Salmonella has been detected in more than 80% of effluent bovine manure immediately post-commercial anaerobic digestion (Chiapetta et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…The Salmonella in raw manure (SL) was below our detection limit of 3 MPN/g while DLE was 55.5 ± 12.5 MPN/g, higher than the microbial standard of 3 MPN/4 g for treated manure (FDA, 2018b). A recent study reported that Salmonella in raw dairy manure ranged from less than 3 Log 10 CFU/g to 5.2 Log 10 CFU/g (Chen et al, 2019). Farm-scale psychrophilic anaerobic digester only reduced Salmonella by 1.2–1.4 Log 10 CFU/g in swine manure (initial Salmonella population ranged from less than 2.0 to 4.7 Log 10 CFU/g), resulting in fair amount of Salmonella remaining in the effluent manure (Masse et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in management practices among the farms may reflect the spatial-temporal clustering of positive samples, highlighting the importance of surveying multiple farms and conducting multi-year studies. However, we found infrequent (low) E. coli O157:H7 prevalence (1.3%), in only poultry and mixed manure samples, whereas other studies reported a prevalence of 15.4% in solid bovine manure from a multi-county survey in California (Chen et al, 2019) and 19% in bovine manure (multiple storage type and ages) in the Southeastern region of the US (Baker et al, 2019). Cattle and other ruminants are commonly considered to be natural reservoirs for non-O157 STEC, with cattle being the major reservoir of E. coli O157:H7 (Hutchison et al, 2005;Jay et al, 2007;Berry et al, 2015Berry et al, , 2019.…”
Section: Pathogen Detection In Manurecontrasting
confidence: 89%
“…Organic fertilizer can accelerate mineralization of organic phosphorus by microorganisms by affecting the activity of soil extracellular phosphatase (Luo et al, 2019). In order to ensure public health and safety, Chen, Biswas, et al (2019) conducted quantitative PCR analysis on the levels of Escherichia coli and Salmonella in untreated cow dung. The level of these two bacteria in untreated cow dung is higher than that in underground samples.…”
Section: Application Of Molecular Biology Methods In Soil Improvementmentioning
confidence: 99%